Freezing Rate Effect on Thermal Transition of Blueberries - Matiacevich, S (Springer, 2015)
World blueberry consumption has risen mainly because of its health benefits (Nicoletta et al. 2008), such as low calories and the presence of anticancer and antioxidant compounds that prevent various diseases, which is why blueberries have become an important component of a healthy diet (Yrjo et al. 1996). Chile is the biggest producer of blueberries in South America and the largest exporter to northern markets (Federación de Productores de Fruta de Chile 2009; Frederick 2009). Blueberries are small blue fruits from the genus Vaccinium, with high nutritional value and potential anti-disease effects, but with a short shelf life of about 20 days under refrigeration conditions at a temperature close to 0 °C (Yommi and Godoy 2010). Due to its short shelf life, conservation methods such as freezing are required. The effect of freezing rates on fruit quality and their optimal conditions are strongly dependent on the type of food. © 2015, Springer Science+Business Media New York.